Geologi Regional Daerah Tamboo, Kecamatan Bonepantai, Kabupaten Bone Bolango, Provinsi Gorontalo - Jingga Hamdata; Ahmad Zainuri; Ronal Hutagalung (-, 2026)
This research was conducted in Tamboo Village, Bonepantai District, Bone Bolango Regency, Gorontalo Province, with the aim of identifying the geological conditions of the study area, including its geomorphology, geological structures, and stratigraphy. The research employed geological field mapping supported by laboratory analyses to obtain comprehensive geological data. The results indicate that the geomorphology of the study area is divided into two geomorphic units, namely the denudational hill unit and the marine coastal plain unit.The denudational hill unit is the dominant landform, covering approximately 70% of the study area. This unit extends in a northwest–southeast direction and is characterized by relatively closely spaced contour patterns and gently rounded slopes formed by denudational processes. In contrast, the marine coastal plain unit occupies approximately 30% of the study area, with elevations ranging from 0 to 50 meters above sea level. This unit developed within a transitional environment between the land and the sea and exhibits the same northwest–southeast distribution.The geological structures identified in the study area are classified as secondary geological structures, represented by the presence of shear fractures and tension fractures. Based on geological age, the stratigraphy of the study area consists of two lithological units, namely Holocene (Quaternary) limestone as the youngest unit and Miocene (Tertiary) andesite as the oldest unit. Overall, the geological conditions of the study area demonstrate a close relationship among lithology, geomorphology, and geological structures, which collectively control the formation and evolution of the landscape.